Against Christianization: Socio-Religious Movements in Magelang after the Java War - Fatkhan, Muhammad; Abdurrahman, Dudung; Hak, Nurul (UIN Sunan Kalijaga Yogyakarta, 2022)
This paper explores the aftermath of the Java War on the socio-religious climate in Magelang. The rate of Christianization in that landscape accelerated following the war between the colonial regime and local residents. The discussion reconsiders the strategies of two leading figures of Nahdlatul Ulama (NU) and Muhammadiyah in stemming Christianization in the 19th-century Magelang. The Christian missionary agenda in Magelang was accomplished by eliciting the community’s sympathy. The missionaries built public hospitals and churches for local residents and hence held the congress of Catholic political associations and De Gereformeerde zending in Midden-Java in Magelang. The Dutch government also issued various policies to suppress Islamic movements. This paper finds that Dalhar Abdurrahman and Ahmad Dahlan responded to the missionary agenda in Magelang with non-confrontational strategies. Dalhar divided the socio-religious landscape of Magelang into two regions, the South and the North, based on the situation of Christian development. Dalhar also build a pesantren in Watucongkol and initiated the foundation of the Magelang Branch of NU to coordinate Muslim reformists. Dahlan halted Christianization by establishing a modern educational institution called Kweekschool Islam in an effort to compete with Dutch schools in Magelang. Dahlan also frequently engaged in dialogues and debates with the Christian missionaries.